Face Authentication by Constructing a 3D Face Image from 2D Face Images, and Encoding a Unique Identification - Menachem Domb (Journal of Systemics, Cybernetics and Informatics)

(untitled)
With the vast spread of automation, the significant demand for communication services, the addition of IoT to the Internet, and the corresponding increase and sophistication in malicious attacks utilizing system vulnerabilities to penetrate systems. Identification and authentication are heavily used in every access trial for electronic resources and communication networks. The traditional approach to coping with such challenges is using passwords, encryption, Secure ID, Firewall, Etc. More safety methods use Biometrics, which suffer from spoofing. The access control market is a fast-growing and highly volatile market that poses significant challenges for investors seeking to make secured decisions. As the market continues to evolve and become more mainstream, there is a growing demand for new identification and authentication technologies. This paper proposes expanding the number of features extracted from a 3D image, with unique features evolved during the generation of the 3D image of the prospect at the access control stage. Experiments support the proposed approach.